Stunning and animal welfare from Islamic and scientific perspectives. - Nakyinsige, Khadijah; Che Man, Yaakob; Aghwan, Zeiad A.; Idrus, Zulkifli; Goh, Yong Meng; Abu Bakar, Fatimah; Sazili, Awis Qurni (Elsevier, 2013)
The transformation of an animal into pieces fit for human consumption is a very important operation. Rather than argue about halal slaughter without stunning being inhumane or stunning being controversial from the Islamic point of view, we discuss slaughter, stunning and animal welfare considering both Islamic and animal welfare legislation requirements. With the world Muslim population close to two billion, the provision of halal meat for the Muslim community is important both ethically and economically. However, from the animal welfare standard point of view, a number of issues have been raised about halal slaughter without stunning, particularly, about stressful methods of restraint and the latency of the onset of unconsciousness. This paper sets out to, discuss the methods of stunning that are acceptable by Islamic authorities, highlight the requirements for stunning to be acceptable in Islam and suggest practical ways to improve the humanness of slaughter